AKUNTABILITAS PUBLIK PENYELENGGARAAN PARKIR TEPI JALAN UMUM DI KOTA PEKALONGAN - Herlambang Dwi Anggara (Magister Administrasi Publik, FISIP, 2019)
Accountability is a problem in many public organizations in Indonesia, including those related to parking issues. Many problems related to parking policy implementation has been faced by many local government in Indonesia. Many researches have been done on parking issues, including those related to street-side parking. However, it is found no research has been found on parking accountability. Therefore, this article is focused on research results on street-side parking in Pekalongan City. The method employed is descriptive qualitative with exploratory paradigm. Is is found that based on the research results and analysis, it is found that accountability principles have not been fully applied. Only one out of four accountability principles which has met requirements, namely transparency. The supporting factors are leadership, regulations, and facilities. The inhibiting factors, however, are limited parking area, less discipline of the street parking personnel, less guidance program, and limited number of government personnels related to parking.